A multicentre programme of clinical and public health research in support of the National Suicide Prevention Strategy for England - D Gunnell; K Hawton; O Bennewith; J Cooper; S Simkin; J Donovan; J Evans; D Longson; S O'Connor; N Kapur (NIHR Journals Library, 2013)
Objectives: To carry out a programme of linked research studies aimed at improving the management of self-harm, reducing the incidence of suicide and providing reliable data to evaluate the impact of the National Suicide Prevention Strategy for England (2002). Methods: There were four research streams: (1) we studied inquest records from 12 coroners and Ministry of Justice data to assess the accuracy of official suicide statistics; (2) we used Office for National Statistics mortality statistics, data from the Multicentre Study of Self-harm in England, national liver unit data, prescription data and patient interviews to assess (a) the impact of paracetamol (acetaminophen) pack size restrictions (1998), (b) the impact of withdrawal of co-proxamol in 2007 and (c) the relative toxicity in overdose of commonly used antidepressants; (3) we carried out 3-month audits of self-harm management in 32 hospitals to investigate variations between hospitals and the impact of management on repeat self-harm; and (4) we developed and piloted letter-based contact interventions aimed at reducing self-harm. Key findings: (1) Between 1990 and 2005, the proportion of researcher-defined suicides given a verdict of suicide by the 12 coroners studied decreased by almost 7%, largely because of the increased use of misadventure/accident verdicts for deaths thought, on clinical review, to be suicides. Use of narrative verdicts increased markedly. Coroners who gave more narrative verdicts also gave fewer suicide verdicts, and geographical variations in the use of narrative verdicts appeared to distort reliable assessment of small-area differences in suicide rates. 2(a) UK legislation to reduce pack sizes of paracetamol was followed by a 43% reduction in number of deaths and a 61% reduction in registrations for liver transplantation over the next 11 years. Paracetamol overdoses were often impulsive and some were influenced by media (including the Internet); sales outlets appeared mostly to be adhering to sales guidance. Smaller pack sizes of paracetamol for sale in Ireland compared with England did not result in a smaller number of tablets being taken in overdose. There was no clear evidence of an effect of the legislation on prescribing of non-steroidal anti-inflammatory drugs, nor on resulting gastrointestinal bleeds. 2(b) Withdrawal of co-proxamol from use in the UK resulted in approximately 600 fewer deaths than predicted between 2005 and 2010 based on previous trends, with no evidence of substitution by poisoning with other analgesics. 2(c) Of the tricyclic antidepressants, dosulepin and doxepin had the greatest toxicity. Citalopram was more toxic than other selective serotonin reuptake inhibitors. (3) There was marked variation between hospitals in the management of self-harm; effects of this variation on patient outcomes were unclear, although psychosocial assessment may have been associated with reduced repetition. Levels of specialist assessment remained static between 2001-2 and 2010-11, but service quality appeared to improve. (4) Findings of two pilot RCTs suggested that, although it would be feasible to scale up these interventions to full trials, these interventions might have low generalisability and be of limited benefit to patients. Conclusion: Within the context of the strengths and limitations of the individual studies, this research programme has made significant additions to the evidence base related to suicide and self-harm prevention in the UK. Study registration: A pilot study of a contact and information based intervention to reduce repeat self-harm; ISRCTN65171515. Funding: The National Institute for Health Research Programme Grants for Applied Research programme.